Sound perception and acoustic comfort in urban spaces in the city of Belo Horizonte, MG - Hirashima, Simone Queiroz da Silveira (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2016)
This paper aims to present and to analyse the responses of users of urban open spaces with regard to the perception of loudness and to the acoustic comfort evaluation, based on data collected during the year 2013, in two squares in the city of Belo Horizonte, MG. During field surveys, acoustic data were measured simultaneously with the application of questionnaires, used to collect subjective and individual variables. The LAeq, T index was used for the characterization of the acoustic environment. The results show that, under the same acoustic conditions, both with regard to the perception of loudness and to the evaluation of acoustic comfort, individuals tend to be more tolerant in the square in which the ambience and the thermal comfort conditions were better. With relation to the perception of loudness, the ranges defined in this study were: Low LAeq < 35 dB (A); Normal 36 < LAeq < 67dB (A); High LAeq > 68 dB (A). Regarding the evaluation of acoustic comfort, the defined ranges were: Comfortable, LAeq < 67 dB (A); and Uncomfortable, LAeq > 68 dB (A). It is expected that these results can contribute to a better understanding of the issues related to acoustic comfort in urban spaces.